Calidad de la información y del sistema de gestión del conocimiento (Revista de Diavulgación L'esprit Ingénieux, 2025)
Information management and quality play a significant role in water resources at the Colombian level. In the municipality of Combita, a methodology proposed by the authors was implemented. This methodology was developed based on the main information gaps identified at the rural level in Colombia.Four key factors are evaluated in the methodology, which are considered essential for information management and quality. Firstly, the creation of a system that allows us to spatially locate and georeference the collected data for better information management by positioning households spatially. This will be carried out using a custom macro and a plan also formulated by the authors. The macro will also enable the recording of consumption and information related to the registered account. The next sub-item to be considered will be land use, as the water demand in this context can be attributed to crops, and it can identify aqueducts for agricultural irrigation or key water exploitation points for the study. The third sub-item will be the identification of the current water intake, which will allow us to understand the access to potable water in rural aqueducts and assess its legality. In rural areas, the exploitation of surface and groundwater for agricultural or livestock purposes is common, and in some cases, it may lack the required water extraction licenses. Finally, an analysis of the current service quality will be conducted. This is of great importance because, in some cases, it involves old pipelines, limited access, intermittent service, or frequent maintenance due to deteriorated pipelines from years of use.The study was conducted in the municipality of Combita (Boyacá), specifically in the San Rafael rural area, which lacks information and control. Hence, it was chosen as the study focal point.